Watermarking technique based on ISB (Intermediate Significant Bit) - Zeki, Akram M.; Abdul Manaf, Azizah; Olanweraju, Rashidah Funke (2010)
Digital watermarking is a special case of the general information hiding problem. It inserts a perceptually transparent pattern called watermark in an image called host or cover using an embedding algorithm. The purpose of the watermark is to supply the ownership of the image or copyright protection information. The energy of the embedded data should be low enough when projected onto the human perception domain but it should be strong enough for robust machine detection. Least Significant Bit (LSB) technique is the earliest developed technique in watermarking and it is also the most simple, direct and common technique. It essentially involves embedding the watermark by replacing the least significant bit of the image data with a bit of the watermark data. The disadvantage of LSB is that it is not robust against attacks. The aim of this study is to develop a robust watermarking model using spatial domain technique and at the same time maintaining important watermarking requirements of picture quality. The new model has been developed based on intermediate significant bit (ISB) aim to replace the watermarked image pixels by new pixels that can protect the watermark data against attacks and at the same time keeping the new pixels very close to the original pixels in order to protect the quality of watermarked image. The technique is based on testing the value of the watermark pixel according to the range of each bit-plane. The main contribution of this research is replacing the classic least significant bits (LSB) technique by a new technique called intermediate significant bits ISB, which improves the robustness and maintains the quality of watermarked images.